2022
DOI: 10.15258/sst.2022.50.2.08
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between seed germination physiological characteristics and germination percentages of direct-seeded hybrid Indica rice under low-temperature and anaerobic interaction

Abstract: Low-temperature and anaerobic conditions are two major limiting factors in the germination of direct-seeded rice. Sixteen hybrid Indica rice varieties were screened and subjected to two different temperatures and oxygen levels. The results revealed that relative to anaerobic conditons, low-temperature is the key limiting factor for seed germination. For all varieties, relative to normal temperature (30°C) and aerobic conditions (89.0% germination), the germination percentages when seeds were germinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Developing novel varieties and hybrids requires the screening and inclusion of genotypes with high germination percentages [ 47 ]. As mentioned in the Results Section, there were high germination percentages for the majority of the 41 maize lines ( Figure 1 ), which is consistent with another study conducted on 16 rice varieties under normal conditions [ 48 ]. The endogenous plant hormones gibberellic acid (GA) and abscisic acid (ABA) are the primary factors that regulate seed dormancy and germination.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Developing novel varieties and hybrids requires the screening and inclusion of genotypes with high germination percentages [ 47 ]. As mentioned in the Results Section, there were high germination percentages for the majority of the 41 maize lines ( Figure 1 ), which is consistent with another study conducted on 16 rice varieties under normal conditions [ 48 ]. The endogenous plant hormones gibberellic acid (GA) and abscisic acid (ABA) are the primary factors that regulate seed dormancy and germination.…”
Section: Discussionsupporting
confidence: 90%
“…The endogenous plant hormones gibberellic acid (GA) and abscisic acid (ABA) are the primary factors that regulate seed dormancy and germination. In particular, low GA/ABA concentrations may trigger seed dormancy, leading to low germination [ 48 ]. Moreover, environmental factors such as light, temperature, soil moisture and pH are known to influence seed germination [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…After dissecting the fruit, we observed that the seed coat color had changed from white to dark brown, indicating a complete post-maturing process [ 37 ]. We speculated that the fruit pulp may weaken the seed’s ability to perceive changes in the external environment, which, together with the isolation of oxygen, limits seed germination [ 38 , 39 ]. For the seed preservation group, the pear seeds reached their highest germination rates of 85% after 100 days of cold stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Drunken horse grass (Achnatherum inebrians) is a common poisonous grass in the Poaceae, and it is widely distributed in the natural grasslands of Northern China [4][5][6]. Studies have shown that this species has invaded more than 85% of the land in some severely degraded areas [7][8][9]. A. inebrians grows rapidly on grasslands, and it competes with other plants for space to grow, nutrients, water, and other resources, which leads to degradation of the grassland and a decrease in high-quality forage [10,11].…”
Section: Introductionmentioning
confidence: 99%